Racial Authoritarian Preemption and the Politics of Tennessee - Sekou Franklin (Social Sciences)
Racial authoritarian preemption occurs when state governments overturn, override, and alter the governing power of racially diverse municipalities. Using Tennessee as a case study, this article looks at the convergence of race, authoritarian governance, and state preemption. Three components of racial authoritarian preemption are examined: anti-federal nullification, administrative fiefdoms, and municipal containment. I focus on the period of 2010–2024, when the Tennessee legislature was captured by conservative Republicans, who then used preemption to revoke locally based civil rights, racial equity initiatives, and redistributive measures championed by minoritized communities. In examining preemption, this article draws from primary and secondary sources, including legislative records and the General Social Survey administered by the University of Chicago’s National Opinion Research Center. The article demonstrates that preemption has been weaponized in the twenty-first century to augment the power of far-right state officials and to disempower cities and municipalities that are racially diverse or dominated by Black-led and multi-racial governing institutions.